Analisis Hidrolis dan Jejak Karbon Jaringan Distribusi Air Bersih di Pulau Kecil Padat Penduduk (Pulau Lengkang Kecil, Kota Batam) - Apritama, Muhammad Rizki; Suryawan, I Wayan Koko; Adicita, Yosef (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2020)
ABSTRACTThe clean water supply system network on Lengkang Kecil Island was developed in 2019.Ã‚Â A small portion of the community's freshwater comes from harvesting rainwater and dug wells, which are only obtained during the rainy season. The primary source of clean water used by the community comes from underwater pipelines with a daily discharge of 0.86 l/sec. The water supply of the Lengkang Kecil Island community is 74.3 m3/day, with 146 House Connections (HCs) and to serve public facilities such as elementary schools, primary health centers, and mosques. Hydraulic evaluation of clean water distribution using EPANET 2.0 software on flow velocity shows the lowest rate of 0.29 m/s and the highest of 1.21 m/s. The lowest pressure value in the distribution system is 6.94-6.96 m and headloss units in the range 0.08-0.25 m/km. These three criteria are still within the distribution network design criteria (feasible). A carbon footprint can be calculated from each activity from the analysis of the evaluation of clean water distribution networks. The most massive emissions came from pumping activities with 131 kg CO2-eq, followed by emissions from wastewater 62.5 kgCO2-eq. Further research is needed to determine the quality of wastewater and the design for a centralized wastewater treatment plant (IPALT) to improve Lengkang Kecil Island residents' living standards.Keywords: Lengkang Kecil Island, water, EPANET, carbon footprintABSTRAKJaringan sistem penyediaan air bersih pada Pulau Lengkang Kecil dimulai pada tahun 2019. Sebagian kecil air bersih yang digunakan masyarakat berasal dari pemanenan air hujan dan sumur gali yang hanya didapat pada musim hujan. Sumber air bersih utama yang digunakan masyarakat berasal dari pengaliran perpipaan bawah laut dengan debit harian 0,86 l/detik. Kebutuhan air masyarakat Pulau Lengkang Kecil adalah 74,3 m3/hari dengan 146 Sambungan Rumah (SR) serta untuk melayani fasilitas umum seperti sekolah dasar (SD), puskesmas, dan masjid. Evaluasi hidrolis distribusi air bersih dengan menggunakan software EPANET 2.0 terhadap kriteria kecepatan aliran menunjukkan nilai terendah 0,29 m/s dan tertinggi 1,21 m/s. Nilai sisa tekan dalam sistem distribusi adalah 6,94Ã¢â‚¬â€œ6,96 m dan unit headloss pada kisaran 0,08Ã¢â‚¬â€œ0,25 m/km. Ketiga kriteria ini masih berada dalam kriteria desain jaringan distribusi (layak). Dari analisis evaluasi jaringan distribusi air bersih, dapat dihitung jejak karbon yang dihasilkan dari setiap kegiatannya. Emisi terbesar berasal dari kegiatan pemompaan dengan nilai 131 kgCO2-eq, diikuti dengan emisi yang berasal dari air limbah dengan nilai 62,5 kgCO2-eq. Penelitian lanjutan diperlukan untuk mengetahui kualitas dari air limbah dan desain untuk instalasi pengolahan air limbah terpusat (IPALT) untuk meningkatkan taraf hidup penduduk Pulau Lengkang Kecil.Kata kunci:Ã‚Â Pulau Lengkang Kecil, air, EPANET, jejak karbon